Placental growth factor and apoptosis as early prognostic factor of placental insufficiency - T. G. Filonenko (Journal of Education, Health and Sport, 2015)
Filonenko T.G., Davydova A.A., Ermola Yu.A., Nechiporenko G.V., Shalanin V.V., Syurina N.A., Menshikova O.P., Kuzmin M.N., Fedotov V.V., Beketov A.A. Placental growth factor and apoptosis as early prognostic factor of placental insufficiency. Journal of Education, Health and Sport. 2015;5(1):69-74. ISSN 2391-8306. DOI: 10.5281/zenodo.13990